An emergency department optimized protocol for qualitative research to investigate care seeking by patients with non‐urgent conditions. Issue 2 (23rd October 2020) - Truter, Piers; Edgar, Dale; Mountain, David; Bulsara, Caroline
Abstract: Aim: To describe a tailored qualitative research methodology for exploring the complex interaction of factors driving non‐urgent care seeking in the emergency department. Design: Qualitative descriptive design with a literature informed semi‐structured interview and analysis structure. Triangulation with the State‐Trait Anxiety Inventory allows expedited exploration of biopsychosocial factors. Consolidated criteria for reporting qualitative research requirements integrated. Methods: With a short 10‐ to 15‐min interview and a low‐inference analysis process, this methodology offers a structured way to explore the "go to ED" decision, to understand the patient perspective on their healthcare needs and feed into the development of suitable local services that meet patient healthcare needs. Results: This methodology offers a structured way for clinician–researchers to explore the factors that influence patients seeking care in the emergency departments for non‐urgent conditions that are specific to their local health service environment. The described methodology is accessible to novice qualitative researchers and includes the semi‐structured interview, coding and analysis frameworks.